PESANTREN AND SOCIAL EMPOWERMENT: A STUDY OF ITS IMPLEMENTATION PROCESS - Sri Widayanti; Siti Muawanah (Balai Penelitian dan Pengembangan Agama Makassar, 2021)
The discussion of the implementation process of social empowerment, which is based on religious belief and critical analysis of social problems, is an interesting discourse. Various faith-based organizations, including pesantren in Indonesia, attempt to contribute to social empowerment to contextualize religious teachings within social life. This research used the qualitative method to describe and analyze the empowerment process, the obstacles during the process, and how religious values and critical analysis affect the empowerment process within pesantren and community. This study resulted in three main points. First, it showed that the stages of empowerment begin with raising critical awareness, analyzing social problems, identifying resources, and building community-based social institutions. Second, it also identified the main principle of empowerment, i.e., democratic, participatory, and community-need-based empowerment programs. Third, it indicated that community participation plays a role as the subject and pesantren as a facilitator of social empowerment.